Entertaining the Trinity Unawares: Genesis xviii in Western Christian Interpretation - Doerfler, Marie E. (The journal of ecclesiastical history, 2014)
Abraham's encounter at Mamre (Genesis xviii.1–16) captivated the Christian imagination from the tradition's very origins. The story hints at God's self-disclosure in a triad of visitors – a theophany that evoked the presence of the Logos or even the Trinity. This article examines late antique exegetical trajectories, focusing upon the interaction between text and expositor in light of the latter's socio-historical context. For patristic exegetes, the Mamre account contained profound spiritual truth if read through the correct doctrinal lens, while presenting a foothold for heresy to the unwary. Changing visions of Trinitarian orthodoxy thus gave rise to new strategies of reading.